Building an Evaluation Model for Hard Power, Soft Power and Climate Change Based on Geopolitical Influence: The Impact of Climate Change on Geopolitical Influence (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Climate change is shaping the new example for future geopolitics with extraordinary drive. Climate change has outperformed the category of unadulterated condition issue and become a central issue in international relations Based on residential and international research on geopolitical influence this investigation built an assessment model that examined the components of hard power, delicate power, and climate change on geopolitical influence. In the wake of choosing records for every one of these components, a Factor Analysis was utilized to figure the geopolitical influence of 30 nations, accounting for the impact of climate change influence. The outcomes appeared Climate change affects the shifting scene of geopolitical influence, however moves in global power can even now be to a great extent identified with previous elements of influence. There are clear contrasts in the degrees of influence among the 30 surveyed nations, and these distinctions can be partitioned into four dimensions. 3. Members in the three climate arranging bunches likewise have their very own progressive systems of influence for instance, EU nations have three particular dimensions, and members in the Umbrella Group fluctuate significantly, as does their position on climate change. This is even more genuine for states that are members of the G77 and China gathering.